Most common intoxications in the geriatric population of Costa Rica from 2015 to 2020: causes, agents and routes of intoxication - Guth Brunner, Thomas (2021)
Objective: To analyze the epidemiologic profile of intoxications of elderly patients in Costa Rica, during the 2015-October 2020 period. Methodology: Data given by the CNCI about the reported intoxications in elderly patients in Costa Rica during the 2015-October 2020 period was analyzed for this investigation. A statistical analysis was then made, with the use of the chi-squared test and the Fisher exact test to analyze the average of intoxications attributed to sodium hypochlorite during the 2020 year period, in comparison to the previous years. Results: The most common cause of intoxications in elderly patients during all the years analyzed was chronic use medications, such as clonazepam, tramadol and insulin. On average, 57.08% of all intoxications in elderly patients happened on women and 42.37% on men. There was an increase in the amount of intoxications reported attributed to sodium hypochlorite in 2020, in comparison to previous years. That difference was statistically significant. Conclusions: Elderly women are at a higher risk than men of suffering an acute intoxication. This can be explained by their higher life expectancy in comparison to men, and also by their increased risk of developing polypharmacy. The most reported intoxications in elderly patients were because of chronic use medications, commonly via oral ingestion. There was a statistically significant increase in the intoxication cases reported attributed to sodium hypochlorite during 2020 in comparison to previous years, which correlates with the start of the COVID-19 pandemic in Costa Rica.